GROSSE AKTA YANG DIBUAT NOTARIS SEBAGAI PENGAKUAN HUTANG DALAM PERJANJIAN KREDIT PADA BANK RAKYAT INDONESIA SAMARINDA - Asmara Sari (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT Asmara Sari, 2014 GROSSE NOTARY DEED ARE MADE AS IN RECOGNITION OF DEBT CREDIT AGREEMENT WITH BANK RAKYAT INDONESIA SAMARINDA. Faculty of Law, University Seventeen August 1945 Samarinda. Supervisor: (1) Abdul MUNIF SH., M. Hum. (2) Sastiono Kesek, SH, LLM.  In the application or implementation is not easy to determine whether grosse deed filed in compliance with the formal requirements and substantive. Especially with regard to the material requirements of the deed grosse. In practice many problematic because of developments in their society grosse deed which is based on a credit agreement of the bank as a principal agreement. Grosse deed of acknowledgment of debt that is overlaid with other agreements such as the power to sell and or authority to install the security rights and others in the grosse deed is not allowed because it causes ambiguous in execution, namely whether the execution was carried out against grosse deed of acknowledgment of debt or the certificate of encumbrance , So this infringe the rules of law set forth in article 224 HIR and fatwa MA No. 213/229/85 / UM-TU / Pdt April 16, 1985 so grosse deed of acknowledgment of debt was not pure debt acknowledgment debtor to the creditor a certain amount and cause the debt recognition grosse deed null and void and the implementation of the execution can not be carried out. And the payment in installments, interest and penalties and other costs to the cost of execution that is overlaid in one grosse deed of acknowledgment of debt can not be justified in accordance with the nature of grosse deed that must be purely unilateral statement of the debtor that recognizes owe certain amount of money to the creditors in accordance with its rules in article 224 HIR and fatwa MA No. 213/229/85 / UM-TU / Pdt April 16, 1985, while the inclusion of a clause on payment in installments, interest and penalties and other costs to the cost of execution should be included in the deed of loan agreement only. The execution procedure grosse deed of acknowledgment of debt does not have to go through the District Court, but in practice it often happens that an application for recognition grosse deed of loan must first pass through the court process and can not be directly applied for the execution of grosse deed of acknowledgment of debt and it will take a long time. While the government bank Bank Rakyat Indonesia Branch Samarinda then be handed over to KPKLN and PUPN, even so when the instasi filed a lawsuit to the District Court, the Court should not be refused on the grounds is not the authority of the Court.